BOTANICAL EXPLORATION IN THE LAMPUNG PROVINCE, SUMATRA - M. Jacobs (Research Center for Biology, 1972)
This is the report of a trip in 1968 conducted by Dr. M. Jacobs of the Rijksherbarium, Leiden, Netherlands, and Dr. B. Prijanto of the Forest Research Institute, Bogor, Indonesia. Financial support was given by the Netherlands Foundation for the Advancement of Tropical Research (WOTRO). Our sincere thanks are due to the liberal way in which this organisation made the enterprise possible, as a continuation of an expedition to the Philippines, on which a report by the same author is now in the press with the journal Blumea.